Modified PowerMax Soil Kit Protocol for DNA Extraction from Sediment or Water Filters v1 - Lauren Lui; Jennifer Kuehl; heidi.smith not provided; Adam Arkin (2025)
This protocol is a modification to the Qiagen PowerMax Soil Kit for extracting DNA from sediment and water filters. It reduces bead-beating to obtain higher quality DNA and less fragmented DNA. Running the DNA out on an agarose gel with a high molecular weight DNA ladder or on a femtopulse is recommended to check DNA quality. This method was published in Wu et al. 2023 Distinct Depth-discrete Profiles of Microbial Communities and Geochemical Insights in the Subsurface Critical Zone AEM (https://doi.org/10.1128/aem.00500-23) and is similar to protocols found in Hug et al. 2015 ISMEJ (https://doi.org/10.1038/ismej.2015.2) and Kantor et al. 2013 mSphere (https://doi.org/10.1128/mbio.00708-13). This was originally developed using the kit by MoBio, but MoBio was bought out by Qiagen and you can purchase the kit from Qiagen now.